Endogenous job contact networks - Andrea Galeotti; Luca Paolo Merlino (University of Essex, Institute for Social and Economic Research (ISER), 2010)
We develop a model where workers, anticipating the possibility of unemployment, invest in connections to access information about available jobs. The investment in connections is high when the job separation rate is moderate, otherwise the investment in connections is low. The response of network investment to labor market conditions generates novel predictions. In particular, the probability that a worker finds a new job via his connections increases in the separation rate, when the separation rate is low, and it decreases otherwise. These predictions are supported by the empirical patterns which we document for the UK labor market.
Keywords: A14; J64; J63; D85; E24; 330; Unemployment; Job search; Endogenous Job Contact Networks; Arbeitslosigkeit; Risiko; Investition; Informationsversorgung; Netzwerk; Großbritannien